The importance of the SSM's fitness and propriety work for banks' performance - evidence from 10 years of SSM work - Vivian van Breemen; Francesca Faella; Christopher Scheins; Claudia Schwarz (European Central Bank (ECB), 2025)
In this paper, we empirically investigate how suitability concerns detected by the SSM in the fitness and propriety of management body appointees impact the performance of European banks in the period 2014-2023. We provide evidence that management body appointees where the assessment of the supervisory authorities raised concerns, had a negative impact on the bank's future performance. The negative effect can be attributed to appointees where the supervisory assessment revealed such severe concerns that ancillary measures were imposed. These results outline the importance of the SSM's work for safeguarding the quality of bank's corporate governance and suggest that the Supervisors seem to be effective in pointing out those appointees that exhibit severe concerns. In addition, we find that the designation of female appointees by supervised entities increased the bank's performance sustainably. This result indicates that stimulating diversity, in terms of gender, in the management bodies of banks positively contributed to bank performance.
Keywords: G21; G28; G30; M14; 330; management body appointees; banking supervision; ancillary measures